Quark Structure of the X (4500), X (4700) and χc(4P,5P) States - Ferretti, J.; Santopinto, E. (Frontiers in Physics, 2021)
We study some of the main properties (masses and open-flavor strong decay widths) of 4P and 5P charmonia. While there are two candidates for the χ c0(4P; 5P) states, the X(4500) and X(4700), the properties of the other members of the χ c(4P; 5P) multiplets are still completely unknown. With this in mind, we start to explore the charmonium interpretation for these mesons. Our second goal is to investigate if the apparent mismatch between the Quark Model (QM) predictions for χ c 0(4P; 5P) states and the properties of the X(4500) and X(4700) mesons can be overcome by introducing threshold corrections in the QM formalism. According to our coupled-channel model results for the threshold mass shifts, the χ c0(5P) ->X(4700) assignment is unacceptable, while the χ c0(4P) as X(4500) or X(4700) assignments cannot be completely ruled out.